Optic chiasm enhancement associated with giant aneurysm and yttrium treated pituitary adenoma. Issue 9 (16th August 2004) - Gabriel, C M; Stevens, J C; Bremner, F; Brew, S; Plant, G T
Abstract : A patient with a history of pituitary tumour treated with yttrium 29 years before presented with an asymmetrical chiasmal neuropathy. Magnetic resonance imaging showed a partially thrombosed giant aneurysm of the right internal carotid artery, with enhancement of the chiasm and right optic tract adjacent to the aneurysm. It was thought that, in addition to the effects of compression, a peri-aneurysmal inflammatory reaction had developed, causing breakdown of the blood–brain barrier and consequent inflammatory changes in the optic chiasm. High dose steroid treatment led to significant improvement in vision within two weeks. Steroids may have a role in the acute preservation of vision in similar cases, as well as in cases of deterioration following coiling or embolisation of aneurysms where thrombosis within the aneurysm has been induced.